2023
DOI: 10.3390/children10071265
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea in Developmental Age: 22-Item Pediatric Sleep Questionnaire for an Observational Descriptive Investigation

Francesca Cremonini,
Ludovica Zucchini,
Federica Pellitteri
et al.

Abstract: The aim of this paper is to perform an observational descriptive study of the Obstructive Sleep Apnea Syndrome (OSAS) in a population of children by evaluating the prevalence and role of sex and age variables. The 22-item Pediatric Sleep Questionnaire (PSQ) was administered to parents of children aged 3 to 12 years. The questionnaire is a very simple tool since it allows for the indication of patients with possible OSAS diagnosis through a cut-off of 0.33. The anonymous diagnostic questionnaire, available in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Childhood OSA disrupts sleep due to upper airway problems, leading to cardiovascular, cognitive, and metabolic issues [ 17 , 18 , 27 , 28 , 29 ]. This can cause endothelial dysfunction, insulin resistance, metabolic problems, daytime sleepiness, and attention deficits [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Childhood OSA disrupts sleep due to upper airway problems, leading to cardiovascular, cognitive, and metabolic issues [ 17 , 18 , 27 , 28 , 29 ]. This can cause endothelial dysfunction, insulin resistance, metabolic problems, daytime sleepiness, and attention deficits [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to Chervin et al’s [ 21 ] initial validation and reliability study, Umano et al [ 22 ] found that the PSQ displayed a remarkable 80% sensitivity and 100% specificity in detecting OSA, while the OSA-18 questionnaire, which is another questionnaire used for OSA diagnosis, showed a sensitivity of 94% and specificity of 55% for OSA diagnosis. These findings have also guided our application in patients, suggesting that in clinical settings with limited access to PSG, the PSQ could be utilized to classify disease severity and identify children in urgent need of sleep evaluation [ 22 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obstructive sleep apnea syndrome (OSAS) is a chronic respiratory disorder characterized by recurrent partial or complete obstructions of the upper airways during sleep. It is a condition that can affect both pediatric [1] and adult patients [2]. Airway obstructions manifest as a reduction (hypopnea) or complete collapse (apnea) of respiratory airflow, accompanied by persistent chest and abdominal respiratory efforts aimed at overcoming the obstructive phenomenon [3].…”
Section: Introductionmentioning
confidence: 99%